Trust Sebagai Pemediasi Pengaruh Service Quality dan Brand Image Terhadap Repurchase Intention Pada Pengguna E-Marketplace di Provinsi Bali - Ida Bagus Wiwekananda; Ida Bagus Udayana Putra; Ni Luh Putu Indiani (Universitas Warmadewa, 2024)
The aim of this research is to analyze the influence of service quality and brand image on repurchase intention with trust as a mediating variable among e-marketplace users in Bali Province. The method used in the research is quantitative with a questionnaire carried out systematically in accordance with the research objectives. The population in this research is the people of Bali Province who have used e-marketplaces for online shopping with a total of 130 respondents. This research uses 5 Likert scales to measure variables when testing the validity and reliability of variables. This research was analyzed using PLS-based SEM. The research results show that (1) Service quality has a positive and significant effect on repurchase intention (2) Brand image has a positive and significant effect on repurchase intention (3) Trust has a positive and significant effect on repurchase intention (4) Service quality has a positive and significant effect on trust (5) Brand image has a positive and significant effect on trust (6) Service quality has a significant effect on repurchase intention through trust (7) Brand image has a significant effect on repurchase intention through trust. It is recommended that future researchers add alternative constructs that influence repurchase intention such as customer satisfaction, e-WOM, price, promotions, etc. as well as increasing references related to research.